2009
DOI: 10.1080/10807030903306984
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate Pesticide Residues in Drinking Water from Artesian Wells and Health Risk Assessment of Agricultural Communities, Thailand

Abstract: Organophosphate pesticide (OPPs) concentrations in artesian wells located in Thai agricultural and non-agricultural communities were studied during both wet and dry seasons. A total of 100 water samples were collected and subjects were asked to complete a survey. Gas chromatography flame photometric detector was used for OPP analysis. The average OPP concentration in the agricultural communities (0.085 and 0.418 µg/l in dry and wet season) was higher than in the non-agricultural communities (0.004 µg/l in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 3 publications
0
20
1
Order By: Relevance
“…Several research studies have documented that, as a result of frequent exposure to OPs, Thai farmers have reported developing these symptoms, as well as nausea/vomiting, tearing, numbness in hands and feet, and chest pain (Jaipieam, et al, 2009a,b; Norkaew, 2010; Taneepanichskul, et al, 2010). Most of these symptoms, although recognized as effects of poisoning, are reversible therefore farmers are unlikely to seek medical attention and often go unreported.…”
Section: Occupational Health Problemmentioning
confidence: 99%
“…Several research studies have documented that, as a result of frequent exposure to OPs, Thai farmers have reported developing these symptoms, as well as nausea/vomiting, tearing, numbness in hands and feet, and chest pain (Jaipieam, et al, 2009a,b; Norkaew, 2010; Taneepanichskul, et al, 2010). Most of these symptoms, although recognized as effects of poisoning, are reversible therefore farmers are unlikely to seek medical attention and often go unreported.…”
Section: Occupational Health Problemmentioning
confidence: 99%
“…9,10 Despite their short half-lives (days to months), OP residues have been found in soils, sediments, and watershedsraising health concerns for chronic and early-life exposure to non-occupational populations especially those living in agricultural communities. 11,12 Hence, rapid and accurate detection of even low-level concentrations of OPs in the environment is critical for effective remediation measures. 13 While there are numerous techniques capable of detecting trace levels of OPs (e.g., gas/liquid chromatography, immunoassays, and mass spectroscopy), these tests are timeconsuming and must be performed in a laboratory by trained technicians.…”
Section: Introductionmentioning
confidence: 99%
“…This concern was prompted by a report of a sharp increase in pesticides used in Thailand over the past two decades [3][4][5] . Furthermore, environmental studies have found pesticide contamination of the soil and water throughout the country, particularly in the central region [6,7] .…”
Section: Introductionmentioning
confidence: 99%